Etiological Factors of Extradural Haematoma: Experience of 80 Cases in Bangladesh (Journal of Science Foundation, 2017)
Background: Extradural haematoma is due to different etiologies.Objectives: The purpose of the present study was to see the etiological factors of extradural haematoma.Methodology: This cross sectional study was conducted in the Department of Neurosurgery at Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2010 to June 2011 for a period of one year and half months. All patients who underwent surgery with traumatic head injury having extradural haematoma were included in the study. At admission, a detailed history of the illness was taken from the patients/patients attendants by face-to-face interview with the help of a preformed questionnaire. Questionnaire was prepared with key variables like age, sex and mode of injury.Result: Eighty (80) patients of traumatic head injury within and after 24 hours of head injury were enrolled in this study. 20(25.1%) patients were present in age group of 11 to 20 years. 19(23.8%) patients were in age group of 21-30 years. 20(25.1%) patients were present in age group of 31 to 40 years. Male was predominant than female which was 60(75.0%) cases and 20(25.0%) cases respectively. The most common mode of injury was road traffic accident which was 51(63.7%) cases followed by fall from height and assault which were 16(20.0%) cases and 13(16.3%) cases respectively.Conclusion: In conclusion RTA is the most common cause of extradural haematoma.Journal of Science Foundation, July 2016;14(2):44-48